- By
**elani** - Follow User

- 90 Views
- Uploaded on

Download Presentation
## PowerPoint Slideshow about '1.4 â Solving Absolute Value Equations' - elani

Download Now**An Image/Link below is provided (as is) to download presentation**

Download Now

Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author.While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server.

- - - - - - - - - - - - - - - - - - - - - - - - - - E N D - - - - - - - - - - - - - - - - - - - - - - - - - -

Presentation Transcript

Example 2 Solve |x – 18| = 5.Example 2 Solve |x – 18| = 5.Example 4 Solve |x + 6| = 3x – 2.Example 4 Solve |x + 6| = 3x – 2.Example 4 Solve |x + 6| = 3x – 2.

1.4 – Solving Absolute Value Equations

Absolute Value

1.4 – Solving Absolute Value Equations

Absolute Value–unit value only

1.4 – Solving Absolute Value Equations

Absolute Value–unit value only

1.4 – Solving Absolute Value Equations

Absolute Value–unit value only (w/o signs)

1.4 – Solving Absolute Value Equations

Absolute Value–unit value only (w/o signs)

ex. |-5| = 5; |5| =

1.4 – Solving Absolute Value Equations

Absolute Value–unit value only (w/o signs)

ex. |-5| = 5; |5| = 5

Example 1

1.4 – Solving Absolute Value Equations

Absolute Value–unit value only (w/o signs)

ex. |-5| = 5; |5| = 5

Example 1

Evaluate 1.4+|5y – 7| if y=-3

1.4 – Solving Absolute Value Equations

Absolute Value–unit value only (w/o signs)

ex. |-5| = 5; |5| = 5

Example 1

Evaluate 1.4+|5y – 7| if y=-3

1.4+|5y – 7|=

1.4 – Solving Absolute Value Equations

Absolute Value–unit value only (w/o signs)

ex. |-5| = 5; |5| = 5

Example 1

Evaluate 1.4+|5y – 7| if y=-3

1.4+|5y – 7|=1.4

1.4 – Solving Absolute Value Equations

Absolute Value–unit value only (w/o signs)

ex. |-5| = 5; |5| = 5

Example 1

Evaluate 1.4+|5y – 7| if y=-3

1.4+|5y – 7|=1.4 +

1.4 – Solving Absolute Value Equations

Absolute Value–unit value only (w/o signs)

ex. |-5| = 5; |5| = 5

Example 1

Evaluate 1.4+|5y – 7| if y=-3

1.4+|5y – 7|=1.4 + |5

1.4 – Solving Absolute Value Equations

Absolute Value–unit value only (w/o signs)

ex. |-5| = 5; |5| = 5

Example 1

Evaluate 1.4+|5y – 7| if y=-3

1.4+|5y – 7|=1.4 + |5(-3)

1.4 – Solving Absolute Value Equations

Absolute Value–unit value only (w/o signs)

ex. |-5| = 5; |5| = 5

Example 1

Evaluate 1.4+|5y – 7| if y=-3

1.4+|5y – 7|=1.4 + |5(-3) – 7|

1.4 – Solving Absolute Value Equations

Absolute Value–unit value only (w/o signs)

ex. |-5| = 5; |5| = 5

Example 1

Evaluate 1.4+|5y – 7| if y=-3

1.4+|5y – 7|=1.4 + |5(-3) – 7|

=1.4

1.4 – Solving Absolute Value Equations

Absolute Value–unit value only (w/o signs)

ex. |-5| = 5; |5| = 5

Example 1

Evaluate 1.4+|5y – 7| if y=-3

1.4+|5y – 7|=1.4 + |5(-3) – 7|

=1.4 +

1.4 – Solving Absolute Value Equations

Absolute Value–unit value only (w/o signs)

ex. |-5| = 5; |5| = 5

Example 1

Evaluate 1.4+|5y – 7| if y=-3

1.4+|5y – 7|=1.4 + |5(-3) – 7|

=1.4 + |-15

1.4 – Solving Absolute Value Equations

Absolute Value–unit value only (w/o signs)

ex. |-5| = 5; |5| = 5

Example 1

Evaluate 1.4+|5y – 7| if y=-3

1.4+|5y – 7|=1.4 + |5(-3) – 7|

=1.4 + |-15 – 7|

1.4 – Solving Absolute Value Equations

Absolute Value–unit value only (w/o signs)

ex. |-5| = 5; |5| = 5

Example 1

Evaluate 1.4+|5y – 7| if y=-3

1.4+|5y – 7|=1.4 + |5(-3) – 7|

=1.4 + |-15 – 7|

=1.4

1.4 – Solving Absolute Value Equations

Absolute Value–unit value only (w/o signs)

ex. |-5| = 5; |5| = 5

Example 1

Evaluate 1.4+|5y – 7| if y=-3

1.4+|5y – 7|=1.4 + |5(-3) – 7|

=1.4 + |-15 – 7|

=1.4 +

1.4 – Solving Absolute Value Equations

Absolute Value–unit value only (w/o signs)

ex. |-5| = 5; |5| = 5

Example 1

Evaluate 1.4+|5y – 7| if y=-3

1.4+|5y – 7|=1.4 + |5(-3) – 7|

=1.4 + |-15 – 7|

=1.4 + |-22|

1.4 – Solving Absolute Value Equations

Absolute Value–unit value only (w/o signs)

ex. |-5| = 5; |5| = 5

Example 1

Evaluate 1.4+|5y – 7| if y=-3

1.4+|5y – 7|=1.4 + |5(-3) – 7|

=1.4 + |-15 – 7|

=1.4 + |-22|

=1.4

1.4 – Solving Absolute Value Equations

Absolute Value–unit value only (w/o signs)

ex. |-5| = 5; |5| = 5

Example 1

Evaluate 1.4+|5y – 7| if y=-3

1.4+|5y – 7|=1.4 + |5(-3) – 7|

=1.4 + |-15 – 7|

=1.4 + |-22|

=1.4 +

1.4 – Solving Absolute Value Equations

Absolute Value–unit value only (w/o signs)

ex. |-5| = 5; |5| = 5

Example 1

Evaluate 1.4+|5y – 7| if y=-3

1.4+|5y – 7|=1.4 + |5(-3) – 7|

=1.4 + |-15 – 7|

=1.4 + |-22|

=1.4 + 22

1.4 – Solving Absolute Value Equations

Absolute Value–unit value only (w/o signs)

ex. |-5| = 5; |5| = 5

Example 1

Evaluate 1.4+|5y – 7| if y=-3

1.4+|5y – 7|=1.4 + |5(-3) – 7|

=1.4 + |-15 – 7|

=1.4 + |-22|

=1.4 + 22

= 23.4

Example 2 Solve |x – 18| = 5.

|x – 18| = 5

Example 2 Solve |x – 18| = 5.

|x – 18| = 5

Example 2 Solve |x – 18| = 5.

|x – 18| = 5

x – 18 = 5 x – 18 = -5

+18 +18 +18 +18

x = 23 x = 13

Example 3

Example 2 Solve |x – 18| = 5.

|x – 18| = 5

x – 18 = 5 x – 18 = -5

+18 +18 +18 +18

x = 23 x = 13

Example 3 Solve |5x – 6| + 9 = 0.

Example 2 Solve |x – 18| = 5.

|x – 18| = 5

x – 18 = 5 x – 18 = -5

+18 +18 +18 +18

x = 23 x = 13

Example 3 Solve |5x – 6| + 9 = 0.

|5x – 6| + 9 = 0

Example 2 Solve |x – 18| = 5.

|x – 18| = 5

x – 18 = 5 x – 18 = -5

+18 +18 +18 +18

x = 23 x = 13

Example 3 Solve |5x – 6| + 9 = 0.

|5x – 6| + 9 = 0

-9 -9

Example 2 Solve |x – 18| = 5.

|x – 18| = 5

x – 18 = 5 x – 18 = -5

+18 +18 +18 +18

x = 23 x = 13

Example 3 Solve |5x – 6| + 9 = 0.

|5x – 6| + 9 = 0

-9 -9

|5x – 6| = -9

Example 2 Solve |x – 18| = 5.

|x – 18| = 5

x – 18 = 5 x – 18 = -5

+18 +18 +18 +18

x = 23 x = 13

Example 3 Solve |5x – 6| + 9 = 0.

|5x – 6| + 9 = 0

-9 -9

|5x – 6| = -9

Note:

Example 2 Solve |x – 18| = 5.

|x – 18| = 5

x – 18 = 5 x – 18 = -5

+18 +18 +18 +18

x = 23 x = 13

Example 3 Solve |5x – 6| + 9 = 0.

|5x – 6| + 9 = 0

-9 -9

|5x – 6| = -9

Note: Absolute value cannot equal a negative number!

Example 2 Solve |x – 18| = 5.

|x – 18| = 5

x – 18 = 5 x – 18 = -5

+18 +18 +18 +18

x = 23 x = 13

Example 3 Solve |5x – 6| + 9 = 0.

|5x – 6| + 9 = 0

-9 -9

|5x – 6| = -9

Note: Absolute value cannot equal a negative number!

Example 2 Solve |x – 18| = 5.

|x – 18| = 5

x – 18 = 5 x – 18 = -5

+18 +18 +18 +18

x = 23 x = 13

Example 3 Solve |5x – 6| + 9 = 0.

|5x – 6| + 9 = 0

-9 -9

|5x – 6| = -9

Note: Absolute value cannot equal a negative number!

|x – 18| = 5

x – 18 = 5 x – 18 = -5

+18 +18 +18 +18

x = 23 x = 13

Example 3 Solve |5x – 6| + 9 = 0.

|5x – 6| + 9 = 0

-9 -9

|5x – 6| = -9

Note: Absolute value cannot equal a negative number!

|x – 18| = 5

x – 18 = 5 x – 18 = -5

+18 +18 +18 +18

x = 23 x = 13

Example 3 Solve |5x – 6| + 9 = 0.

|5x – 6| + 9 = 0

-9 -9

|5x – 6| = -9

Note: Absolute value cannot equal a negative number!

Example 2 Solve |x – 18| = 5.

|x – 18| = 5

x – 18 = 5 x – 18 = -5

+18 +18 +18 +18

x = 23 x = 13

Example 3 Solve |5x – 6| + 9 = 0.

|5x – 6| + 9 = 0

-9 -9

|5x – 6| = -9

Note: Absolute value cannot equal a negative number!

x = Ø

Example 4 Solve |x + 6| = 3x – 2.

|x + 6| = 3x – 2

Example 4 Solve |x + 6| = 3x – 2.

|x + 6| = 3x – 2

Example 4 Solve |x + 6| = 3x – 2.

|x + 6| = 3x – 2

x + 6 = 3x – 2 x + 6 = -(3x – 2)

x + 6 = -3x – (-2)

Example 4 Solve |x + 6| = 3x – 2.

|x + 6| = 3x – 2

x + 6 = 3x – 2 x + 6 = -(3x – 2)

x + 6 = -3x – (-2)

x + 6 = 3x – 2

Example 4 Solve |x + 6| = 3x – 2.

|x + 6| = 3x – 2

x + 6 = 3x – 2 x + 6 = -(3x – 2)

x + 6 = -3x – (-2)

x + 6 = 3x – 2 x + 6

Example 4 Solve |x + 6| = 3x – 2.

|x + 6| = 3x – 2

x + 6 = 3x – 2 x + 6 = -(3x – 2)

x + 6 = -3x – (-2)

x + 6 = 3x – 2 x + 6 = -3x

Example 4 Solve |x + 6| = 3x – 2.

|x + 6| = 3x – 2

x + 6 = 3x – 2 x + 6 = -(3x – 2)

x + 6 = -3x – (-2)

x + 6 = 3x – 2 x + 6 = -3x + 2

Example 4 Solve |x + 6| = 3x – 2.

|x + 6| = 3x – 2

x + 6 = 3x – 2 x + 6 = -(3x – 2)

x + 6 = -3x – (-2)

x + 6 = 3x – 2 x + 6 = -3x + 2

-3x -3x

Example 4 Solve |x + 6| = 3x – 2.

|x + 6| = 3x – 2

x + 6 = 3x – 2 x + 6 = -(3x – 2)

x + 6 = -3x – (-2)

x + 6 = 3x – 2 x + 6 = -3x + 2

-3x -3x

-2x + 6 = -2

Example 4 Solve |x + 6| = 3x – 2.

|x + 6| = 3x – 2

x + 6 = 3x – 2 x + 6 = -(3x – 2)

x + 6 = -3x – (-2)

x + 6 = 3x – 2 x + 6 = -3x + 2

-3x -3x

-2x + 6 = -2

- 6 -6

Example 4 Solve |x + 6| = 3x – 2.

|x + 6| = 3x – 2

x + 6 = 3x – 2 x + 6 = -(3x – 2)

x + 6 = -3x – (-2)

x + 6 = 3x – 2 x + 6 = -3x + 2

-3x -3x

-2x + 6 = -2

- 6 -6

-2x

Example 4 Solve |x + 6| = 3x – 2.

|x + 6| = 3x – 2

x + 6 = 3x – 2 x + 6 = -(3x – 2)

x + 6 = -3x – (-2)

x + 6 = 3x – 2 x + 6 = -3x + 2

-3x -3x

-2x + 6 = -2

- 6 -6

-2x = -8

Example 4 Solve |x + 6| = 3x – 2.

|x + 6| = 3x – 2

x + 6 = 3x – 2 x + 6 = -(3x – 2)

x + 6 = -3x – (-2)

x + 6 = 3x – 2 x + 6 = -3x + 2

-3x -3x

-2x + 6 = -2

- 6 -6

-2x = -8

-2 -2

Example 4 Solve |x + 6| = 3x – 2.

|x + 6| = 3x – 2

x + 6 = 3x – 2 x + 6 = -(3x – 2)

x + 6 = -3x – (-2)

x + 6 = 3x – 2 x + 6 = -3x + 2

-3x -3x

-2x + 6 = -2

- 6 -6

-2x = -8

-2 -2

x = 4

Example 4 Solve |x + 6| = 3x – 2.

|x + 6| = 3x – 2

x + 6 = 3x – 2 x + 6 = -(3x – 2)

x + 6 = -3x – (-2)

x + 6 = 3x – 2 x + 6 = -3x + 2

-3x -3x+3x +3x

-2x + 6 = -2

- 6 -6

-2x = -8

-2 -2

x = 4

Example 4 Solve |x + 6| = 3x – 2.

|x + 6| = 3x – 2

x + 6 = 3x – 2 x + 6 = -(3x – 2)

x + 6 = -3x – (-2)

x + 6 = 3x – 2 x + 6 = -3x + 2

-3x -3x+3x +3x

-2x + 6 = -2 4x

- 6 -6

-2x = -8

-2 -2

x = 4

Example 4 Solve |x + 6| = 3x – 2.

|x + 6| = 3x – 2

x + 6 = 3x – 2 x + 6 = -(3x – 2)

x + 6 = -3x – (-2)

x + 6 = 3x – 2 x + 6 = -3x + 2

-3x -3x+3x +3x

-2x + 6 = -2 4x + 6

- 6 -6

-2x = -8

-2 -2

x = 4

Example 4 Solve |x + 6| = 3x – 2.

|x + 6| = 3x – 2

x + 6 = 3x – 2 x + 6 = -(3x – 2)

x + 6 = -3x – (-2)

x + 6 = 3x – 2 x + 6 = -3x + 2

-3x -3x+3x +3x

-2x + 6 = -2 4x + 6 = 2

- 6 -6

-2x = -8

-2 -2

x = 4

Example 4 Solve |x + 6| = 3x – 2.

|x + 6| = 3x – 2

x + 6 = 3x – 2 x + 6 = -(3x – 2)

x + 6 = -3x – (-2)

x + 6 = 3x – 2 x + 6 = -3x + 2

-3x -3x+3x +3x

-2x + 6 = -2 4x + 6 = 2

- 6 -6 - 6 -6

-2x = -8

-2 -2

x = 4

Example 4 Solve |x + 6| = 3x – 2.

|x + 6| = 3x – 2

x + 6 = 3x – 2 x + 6 = -(3x – 2)

x + 6 = -3x – (-2)

x + 6 = 3x – 2 x + 6 = -3x + 2

-3x -3x+3x +3x

-2x + 6 = -2 4x + 6 = 2

- 6 -6 - 6 -6

-2x = -8 4x = -4

-2 -2

x = 4

Example 4 Solve |x + 6| = 3x – 2.

|x + 6| = 3x – 2

x + 6 = 3x – 2 x + 6 = -(3x – 2)

x + 6 = -3x – (-2)

x + 6 = 3x – 2 x + 6 = -3x + 2

-3x -3x+3x +3x

-2x + 6 = -2 4x + 6 = 2

- 6 -6 - 6 -6

-2x = -84x = -4

-2 -2 4 4

x = 4

Example 4 Solve |x + 6| = 3x – 2.

|x + 6| = 3x – 2

x + 6 = 3x – 2 x + 6 = -(3x – 2)

x + 6 = -3x – (-2)

x + 6 = 3x – 2 x + 6 = -3x + 2

-3x -3x+3x +3x

-2x + 6 = -2 4x + 6 = 2

- 6 -6 - 6 -6

-2x = -84x = -4

-2 -2 4 4

x = 4 OR x = -1

Example 4 Solve |x + 6| = 3x – 2.

|x + 6| = 3x – 2

x + 6 = 3x – 2 x + 6 = -(3x – 2)

x + 6 = -3x – (-2)

x + 6 = 3x – 2 x + 6 = -3x + 2

-3x -3x+3x +3x

-2x + 6 = -2 4x + 6 = 2

- 6 -6 - 6 -6

-2x = -84x = -4

-2 -2 4 4

x = 4 OR x = -1

Example 4 Solve |x + 6| = 3x – 2.

|x + 6| = 3x – 2

x + 6 = 3x – 2 x + 6 = -(3x – 2)

x + 6 = -3x – (-2)

x + 6 = 3x – 2 x + 6 = -3x + 2

-3x -3x+3x +3x

-2x + 6 = -2 4x + 6 = 2

- 6 -6 - 6 -6

-2x = -84x = -4

-2 -2 4 4

x = 4 OR x = -1

|x + 6| = 3x – 2

x + 6 = 3x – 2 x + 6 = -(3x – 2)

x + 6 = -3x – (-2)

x + 6 = 3x – 2 x + 6 = -3x + 2

-3x -3x+3x +3x

-2x + 6 = -2 4x + 6 = 2

- 6 -6 - 6 -6

-2x = -84x = -4

-2 -2 4 4

x = 4 OR x = -1

|x + 6| = 3x – 2

x + 6 = 3x – 2 x + 6 = -(3x – 2)

x + 6 = -3x – (-2)

x + 6 = 3x – 2 x + 6 = -3x + 2

-3x -3x+3x +3x

-2x + 6 = -2 4x + 6 = 2

- 6 -6 - 6 -6

-2x = -84x = -4

-2 -2 4 4

x = 4 OR x = -1

|x + 6| = 3x – 2

x + 6 = 3x – 2 x + 6 = -(3x – 2)

x + 6 = -3x – (-2)

x + 6 = 3x – 2 x + 6 = -3x + 2

-3x -3x+3x +3x

-2x + 6 = -2 4x + 6 = 2

- 6 -6 - 6 -6

-2x = -84x = -4

-2 -2 4 4

x = 4 OR x = -1

Download Presentation

Connecting to Server..